PENGARUH KUALITAS PRODUK, PROMOSI DAN HARGA TERHADAP PENJUALAN KAROSERI WING BOX DI PT. MITRA TOYOTAKA INDONESIA - Haryo Setyaka (JURNAL LENTERA BISNIS, 2017)
This study aims to examine and analyze the influence of the quality of products, promotions and pricing to sales product karoseri Wing Box at PT. Toyotaka Mitra Indonesia. The data used in this study was a questionnaire distributed to clients of PT. Toyotaka Mitra Indonesia as many as 95 respondents. The sampling method used was accidental sampling. The analytical method used in this research is multiple linear regression analysis using SPSS software application assistance. The results showed the quality of products, promotions and price together (simultaneously) significantly affect sales. Partially quality of products significantly influence sales with positive relationships, while sale prices and partially no significant influence on sales and promotions and price relationship is positive for sales.Keywords : quality of product, promotion, pricing, sales